The complete mitochondrial genome of the pallid seahorse Solegnathus hardwickii (Actinopterygii; Syngnathiformes; Syngnathidae) obtained using next-generation sequencing - Alireza Asem; Yun-Sheng Xu; Pei-Zheng Wang; Weidong Li (Mitochondrial DNA. Part B. Resources, 2018)
The complete mitochondrial genome of Solegnathus hardwickii was determined to be 16,519 bp long circular molecule with a typical gene arrangement of vertebrate mitochondrial. The complete mitochondrial genomes were obtained by conventional and long PCR. Tree constructed using maximum likelihood based on protein-coding genes and ribosomal RNAs showed close relationship of S. hardwickii with Hippocampus spp.